Seasonal Abundance and Spatial Pattern of Distribution of Liriomyza trifolii (Diptera: Agromyzidae) and Its Parasitoid on Bean and Squash in South Florida - Shashan Devkota; Dakshina Seal (Turkish Journal of Agriculture: Food Science and Technology, 2021)
American serpentine leafminer, Liriomyza trifolii, is a polyphagous insect pest that feeds on a wide range of vegetable and ornamental plants around the world. To develop an effective IPM program, information on the seasonal field distribution and population dynamics of leafminer and its parasitoids is very important. Therefore, seasonal abundances and spatial distributions of, L. trifolii on snap bean and squash were studied during four crop growing periods between 2013 to 2015 in Homestead, Florida. The mean numbers of mines, larvae, pupae, emerged adults, and parasitoids on snap bean were highest at 2 weeks after planting during all four growing periods. Whereas, the mean numbers of mines, larvae, pupae, emerged adults, and parasitoids on squash were highest at 3 weeks after planting during all four growing periods. L. trifolii distributions tended to be aggregated on snap bean at 2 weeks after planting during most of growing periods but had uniform distributions on squash at 2 weeks after planting during most of growing periods. Similar results were seen on the distribution of leafminer parasitoids on both bean and squash.